Pengaruh manajemen kinerja perpustakaan terhadap kepuasan pemustaka di Perpustakaan UIN Antasari Banjarbaru - Norjannah, Widya (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2023)
The development of the times is marked by various change in various aspects of social life. Libraries, an organization that focuses on serving users, must adapt to developments so as not to be left behind. In serving users, it is of course important to pay attention to library performance management, because it is one of the benchmarks for user satisfaction. Quantitative method, which aims to show the relationship of influence between 2 variables. The population includes active students of UIN Antasari Banjarmasin (campus 2 Banjarbaru ) with a sample of 30 people. Using non probability sampling, namely purposive sampling. By distributing closed questionnaires using a Likert scale. This research is objective and includes quantitative data collection, analysis, and statistical testing with assistance from IBM SPSS Statistics Software 21. this research shows the influence that library performance management has on user satisfaction with an R Square of 72.8% , meaning management library own strong influence to satisfaction user . The influence of library performance management on user satisfaction is 72.8% , while the remaining 27.2% (100% - 72.8%) is influenced by other variables outside this research. So according to Chin (1988) the R-Square value of 72.8% is included in the strong category. Suggestions for future researchers could be to conduct research with a larger sample, because the population of this study is quite a large number of students at UIN Antasari Banjarbaru.